COLLABORATIVE APPROACH TO FLEXIBILITY, VISIBILITY AND VELOCITY IN SUPPLY CHAINS: A MULTI-GROUP ANALYSIS - Jonathan Ehimen EKPUDU; Ekpenyong Ekpenyong UDOFIA (Modern Management Review, 2023)
Most studies focus on developed economies when investigating resilience, creating a gap in research in developing countries. This study addresses two literature gaps by examining supplier collaboration's effect on supply chain flexibility, visibility, and velocity in an African business environment and assessing the relevance of company size to this relationship. This study used a descriptive design. The population and sample were 1332 and 264 respectively. 219 questionnaire copies informed the analysis and it was performed using percentages and a structural equation model. The study reveals that resource sharing is the most effective strategy for improving supply chain resilience and collaboration practices are most effective for supply chain flexibility. Organisations pursuing supply chain resilience can implement resource-sharing and information-sharing strategies to yield resilience. Additionally, managers must note that supplier collaboration may not yield similar results across all resilience performance measurements. Medium-scale firms must focus on information sharing to improve supply chain flexibility.